2010
DOI: 10.1051/0004-6361/200913298
|View full text |Cite
|
Sign up to set email alerts
|

The X-ray to optical-UV luminosity ratio of X-ray selected type 1 AGN in XMM-COSMOS

Abstract: We present a study of the X-ray to optical properties of a sample of 545 X-ray selected type 1 AGN, from the XMM-COSMOS survey, over a wide range of redshifts (0.04 < z < 4.25) and X-ray luminosities (40.6 ≤ Log L [2−10] keV ≤ 45.3). About 60% of them are spectroscopically identified type 1 AGN, while the others have a reliable photometric redshift and are classified as type 1 AGN on the basis of their multi-band Spectral Energy Distributions. We discuss the relationship between UV and X-ray luminosity, as par… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

42
284
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 359 publications
(336 citation statements)
references
References 75 publications
42
284
1
Order By: Relevance
“…We find that the black hole X-ray luminosities (direct proxies of the accretion rates) are correlated with the host galaxy star formation rate -in accordance with the similar shapes of the cosmic star formation and black hole accretion rate density -albeit with a large scatter. Current observations probe a too narrow dynamic range in X-ray luminosities to see this correlation, even though it can be inferred if the spectroscopically confirmed COSMOS data (Lusso et al 2010(Lusso et al , 2011Brusa et al 2010;Bongiorno et al 2012) at all redshifts are combined together. Large scatter seen in the simulated SF R -L 2−10keV relation demonstrates that the physical link between star formation and black hole accretion triggering is more complex than previously envisaged.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…We find that the black hole X-ray luminosities (direct proxies of the accretion rates) are correlated with the host galaxy star formation rate -in accordance with the similar shapes of the cosmic star formation and black hole accretion rate density -albeit with a large scatter. Current observations probe a too narrow dynamic range in X-ray luminosities to see this correlation, even though it can be inferred if the spectroscopically confirmed COSMOS data (Lusso et al 2010(Lusso et al , 2011Brusa et al 2010;Bongiorno et al 2012) at all redshifts are combined together. Large scatter seen in the simulated SF R -L 2−10keV relation demonstrates that the physical link between star formation and black hole accretion triggering is more complex than previously envisaged.…”
Section: Resultsmentioning
confidence: 93%
“…We compare the Illustris results with the recent study by Azadi et al (2014) based on the PRIMUS survey (green diamonds) and with the COSMOS data compilation (Lusso et al 2010(Lusso et al , 2011, with stellar masses and star formation rates from Bongiorno et al 2012 and redshifts from Brusa et al 2010; red circles). The three panels are for different redshift intervals probed by the surveys while we plot the Illustris data at the mean redshift of each redshift bin.…”
Section: The Link Between Star Formation and Agn Triggeringmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is not clear whether such a linear relation holds for more luminous AGNs (i.e.,quasars 14 ). Notably, studies comparing L X to the UV luminosity for AGNs found that the ratio between the X-ray and UV luminosities rapidly decreases with increasing UV luminosity for type 1 AGNs (e.g., Tananbaum et al 1979;Strateva et al 2005;Lusso et al 2010). Since the rest-frame mid-IR emission of AGNs originates from the hot dust heated by the UV photons from the SMBH accretion disk, understanding the L L X MIR -relation for luminous AGNs is also crucial for understanding the structure of the hot dust surrounding the central SMBH, as well as the AGN accretion physics.…”
Section: Introductionmentioning
confidence: 99%
“…We use type 1 AGN samples from the AGN and Galaxy Evolution Survey (AGES; Kochanek et al 2012) in the Boötes survey region, the publicly available AGN samples from the XMM-COSMOS survey (Lusso et al 2010), the XMM-XXL-North survey (Liu et al 2016;Menzel et al 2016;Pierre et al 2016), and the SDSS DR5 quasars with serendipitous Swift/XRT observations (Wu et al 2012a). …”
Section: Introductionmentioning
confidence: 99%